2023
DOI: 10.3390/nu15051158
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Prebiotics and Synbiotics Supplementation on the Immune Function of Male University Football Players

Abstract: This study was conducted to compare the effects of long-term prebiotic and synbiotic supplementations on the immunosuppression of male football players after daily high-intensity training and a one-time strenuous exercise. A total of 30 male university student-athletes were recruited and randomly assigned to the prebiotic (PG, n = 15) or synbiotic group (SG, n = 15), receiving a prebiotic or synbiotic once per day for six weeks. Physiological assessments were conducted by a maximal oxygen uptake (VO2max) test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The speed and grade started at 2.7 km/h and 10%, respectively, and were increased every 3 min until the participant developed volitional fatigue. The test would terminate when the participant reached the following criteria (at least three) 19 , 20 : (1) with workload rising, VO 2 was no longer rising or rose less than 2 ml/kg/min; (2) maximal heart rate reached age-predicted maximum heart rate: 220-age; (3) respiratory exchange ratio (RER) > 1.15; (4) rating of perceived exertion (RPE) ≥ 18. Oxygen uptake output was based on breath-by-breath analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The speed and grade started at 2.7 km/h and 10%, respectively, and were increased every 3 min until the participant developed volitional fatigue. The test would terminate when the participant reached the following criteria (at least three) 19 , 20 : (1) with workload rising, VO 2 was no longer rising or rose less than 2 ml/kg/min; (2) maximal heart rate reached age-predicted maximum heart rate: 220-age; (3) respiratory exchange ratio (RER) > 1.15; (4) rating of perceived exertion (RPE) ≥ 18. Oxygen uptake output was based on breath-by-breath analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a study compared the effects of long-term (6 weeks) prebiotic and synbiotic supplementation on the immune function of male football players after daily high-intensity training and a one-time strenuous exercise, finding that supplementation with synbiotics is better than with prebiotics at improving immune function by reducing the incidence of URTI and increasing the SIgA level. Results also showed that synbiotics could reverse the detrimental outcomes of one-time strenuous exercise [ 135 ]. Moreover, a triple-blinded study conducted by Quero et al revealed that professional soccer players administered synbiotics ( Bifidobacterium lactis CBP001010, Lactobacillus rhamnosus CNCM I-4036, Bifidobacterium longum ES1, and fructo-oligosaccharides) exhibited markedly improved anxiety, stress, and sleep quality [ 100 ].…”
Section: Dietary Recommendations For Targeting Of the Gut Microbiotamentioning
confidence: 99%
“…In humans, Hadzic et al [56] found that 17 g/day of soluble dietary fiber during a 4-week period improved the rating of perceived exertion but had no effect on neuromuscular and cardiovascular endurance. Zhang et al [57] verified the effect of prebiotic supplementation against synbiotic (a mixture comprising live microorganisms and substrate (s) selectively utilized by host microorganisms that confers a health benefit on the host [58]) supplementation on exercise and immune-related parameters. The V ˙O2max did not differ within and between groups, but both prebiotic and symbiotic supplements decreased IL-4, IL-10, and transforming growth factor-b1.…”
Section: Strategies For Manipulating the Microbiome In Athletesmentioning
confidence: 99%